Bridging the gap between policy logic and stakeholder perceptions: a dual assessment of ecosystem services in Chengdu’s peri-urban agricultural areas - Lyu, Ran; Hussein, Mohd Kher; Abdul Shukor, Shureen Faris; Zhuang, Qianda; Yang, Huihua (Frontiers Media SA, 2026)
Peri-urban landscape planners are increasingly aware of the value of ecosystem services in improving the quality of life of urban residents and strengthening the protection of peri-urban agriculture. However, the ecosystem service framework in China has not yet been systematically integrated into agricultural spatial planning. Therefore, this study aims to assess the ecosystem services in peri-urban agricultural areas and the specific objectives are (1) to assess the way the ecosystem services framework is implemented in the current agricultural land use planning in Chengdu city and (2) to assess the importance of the current peri-urban agroecosystem services with case study in Chengdu Eco-Zone. This study conducted a case study of Chengdu Eco-Zone in China combined document analysis and interview method. Firstly, 8 strategic documents related to land planning in Chengdu were selected for analysis, secondly, 36 planners and practitioners were interviewed. Analyses of agriculture-related planning documents revealed that the term ‘ecosystem services’ is not explicitly mentioned in formal planning documents at present. Still, the content of the most recent strategic documents reflects the relevance of the ecosystem services framework. In assessing agro-spatial ecosystem services, as represented by the Chengdu Eco-Zone, the cultural services provided by the respondents have the highest value (100%), followed by supporting services (94.44%) and regulating services (94.44%), while the value of provisioning services is slightly lower (62.04%). Our findings suggest that incorporating the concept of ecosystem services and using a people-centred valuation approach in planning urban and peri-urban agricultural land can promote the conservation of existing agricultural land and communicate the benefits that peri-urban agricultural areas provide citizens at all levels of agricultural spatial governance.